1984
DOI: 10.1099/00221287-130-10-2535
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cell Cycle Events in Synchronized Cultures of Anacystis nidulans

Abstract: Synchronized cultures of Anacystis niduians (Synechococcus PCC 6301) were induced by a lightdark incubation scheme under moderate light intensity (3.2 J rn-? s-'). At incubation temperatures of 32 OC. 35 "C and 38 "C, typical step-wise growth cycles were observed at growth rates of 8, 6 and 4 h doubling times, respectively. Using the same method of inducing cell synchrony but under increased light intensity (4.8 J m-s-I) , cell number increased exponentially and growth rates were twice as high as those at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…The lack of synchronous cell division upon release of dark-blocked Synechococcus cells into the light contrasts with some of the results of others (2,3,18,20), but the experimental conditions were not identical in these cases.…”
Section: Resultsmentioning
confidence: 38%
See 1 more Smart Citation
“…The lack of synchronous cell division upon release of dark-blocked Synechococcus cells into the light contrasts with some of the results of others (2,3,18,20), but the experimental conditions were not identical in these cases.…”
Section: Resultsmentioning
confidence: 38%
“…3G). Furthermore, at all but the highest growth rate examined, Light Intensity (,uE m-2 s-i) 4 the balanced-growth DNA frequency distributions contained distinct peaks (Fig. 3C to G), indicative of gaps in DNA synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…During the first 8 h after the dark to light shift, protein, RNA and DNA synthesis are sequentially initiated followed by cell septum formation, which is usually completed after 8 h (Asato, 1983). Subsequent cell cycles manifest the same sequences of cell events (Asato, 1979). Synchronized DNA synthesis within the synchronized cell cycle has been demonstrated in A .…”
Section: Introductionmentioning
confidence: 82%
“…nidulans by others (Herdman et al, 1970;Herdman & Carr, 1971 ;Delaney & Carr, 1975 ;Gleason & Ooka, 1978;Bagi et al, 1979). Phospholipid (Asato, 1979) and cell wall synthesis (Asato, 1984) and peak rates of O2 evolution (Csatorday & Horvath, 1977) also occur at specific times within the cell cycle. It was concluded that the periods of macromolecular synthesis are major events in the cell developmental cycle of A .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation